Ocena efektywności inwestycji zależnych ekonomicznie - Zarzecki, Dariusz (Economically Dependent Investments Appraisal, 2008)
Traditional investment appraisal techniques require some modifications when two investments being appraised are economically dependent. There are two basic forms of dependency. If a decision to undertake the second investment will increase the benefits expected from the first (or decrease the costs of undertaking the first without changing the benefits), the second investment is said to be a complement of the first. If the decision to undertake the second investment will decrease the benefits expected from the first (or increase the costs of undertaking the first without changing the benefits), the second is said to be a substitute for the first. In the extreme cases, the two investments are said to be mutually exclusive (full substitution) or the first investment can be said to be a prerequisite of the second. The paper deals with the ways of overcoming difficulties resulting from dependency of investments.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1200, s. 623-630